2004
DOI: 10.1111/j.1098-1616.2004.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

University‐Provided Retirement Planning Support and Retiree Financial Satisfaction During Retirement: Differences by Gender, Job Classification, and Planning Behavior

Abstract: Sound financial planning and financial advice is necessary to achieve retirement income adequacy. The shift from defined benefit to defined contribution pension plans and the recent bankruptcy of Enron Corporation underscore the importance of managing retirement accumulation and liquidation risks. This study analyzes the effectiveness and adequacy of institutional-provided information and advice on employees' retirement planning decisions and their satisfaction with financial resources during retirement. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…31 Gender, planning practices, job classifi cation and age were signifi cant predictors of fi nancial satisfaction during retirement. Meanwhile, Giancola indicated that in general men were at a more advantageous position in retirement planning as compared to female counterparts, as they relatively earned more and in return saved more for retirement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…31 Gender, planning practices, job classifi cation and age were signifi cant predictors of fi nancial satisfaction during retirement. Meanwhile, Giancola indicated that in general men were at a more advantageous position in retirement planning as compared to female counterparts, as they relatively earned more and in return saved more for retirement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poor financial behavior of many Americans may be attributed to ignorance or a lack of understanding how to make good financial decisions (Edmiston and Gillett-Fisher, 2006). This information asymmetry negatively impacts retirement plan participation, contribution levels, when retirement planning begins in an employee's career, and the value added from employer-provided retirement information and advice (Power and Hira, 2004).…”
Section: Background Methods and Study Designmentioning
confidence: 99%
“…Research also documents a positive relationship between participation in financial literacy programs and retirement preparedness (Bernheim and Garrett, 2003). Power and Hira (2004) show that retirement planning should begin earlier in an employee's career and that employer‐provided retirement information and advice is a highly valued service. A Watson Wyatt Worldwide study concludes that companies with good benefit plans tend to serve their shareholders and employees better and that an important element of a good plan is good education and advice (Watson Wyatt Worldwide, 2005).…”
Section: Background Hypotheses and Methodsmentioning
confidence: 99%